2020
DOI: 10.1111/1759-7714.13595
|View full text |Cite
|
Sign up to set email alerts
|

Oral leukoplakia and the long‐term risk of upper gastrointestinal cancer deaths in the Linxian dysplasia population

Abstract: Background: To investigate oral leukoplakia (OL) and risk of upper gastrointestinal (UGI) cancer deaths in the Linxian Dysplasia Nutrition Intervention Trial (NIT) cohort. Methods: A total of 3318 subjects with esophageal squamous dysplasia enrolled on 1 May 1985, and were followed up until 30 September 2015. Participants with OL at baseline were treated as an exposed group, while the remainder was selected as a control group. All subjects were followed monthly and reviewed quarterly by the Linxian Cancer Regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Thirdly, socioeconomic status (SES) is a major confounder and a powerful determinant of common chronic diseases. Despite we included education level as a surrogate factor of SES according to the previous study, [ 44 ] the confounding bias caused by missing SES information needs to be acknowledged. Finally, other baseline information was collected by questionnaire, which may lead to a limited extrapolation of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, socioeconomic status (SES) is a major confounder and a powerful determinant of common chronic diseases. Despite we included education level as a surrogate factor of SES according to the previous study, [ 44 ] the confounding bias caused by missing SES information needs to be acknowledged. Finally, other baseline information was collected by questionnaire, which may lead to a limited extrapolation of our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, research on the relationship between risk factors and UGI cancer in the dysplasia population is limited. Some studies have suggested that body mass index, oral leukoplakia, and tooth loss increase the risk of death from UGI cancer in this population ( 6 , 19 , 22 ). However, no study suggests the association between family history of UGI cancer and the risk of its death.…”
Section: Introductionmentioning
confidence: 99%
“…Through the comparison of the general group and dysplasia group in the Linxian Nutrition Intervention Trial, we found differences of age, body mass index, alcohol consumption, and fresh vegetable intake between the two groups ( 8 , 17 , 18 ). By comparing the incidence and death of cancers in these two groups, with 30 years of follow-up, it was found that esophageal cancer death in the general population accounted for 44.47% of the total death of malignant cancers and the death of gastric cancer accounted for 33.48%, while in high-risk groups, esophageal cancer and gastric cancer accounted for 51.2% and 34.0%, respectively ( 6 , 19 ). At present, studies on the relationship between risk factors and UGI cancer in the general population have provided reliable and sufficient information ( 8 , 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations of nitrate and nitrite in water are a common characteristic among most countries with a high GC incidence, such as Chile, Costa Rica, and Japan [ 17 ]. Linxian, a rural county of Anyang, Henan Province, is one of the high-incidence regions of upper gastrointestinal (UGI) cancer in China [ 18 ]. The region's arid climate and low annual rainfall make surface water, such as mountain spring water and shallow well water, the primary water resource [ 19 ].…”
Section: Introductionmentioning
confidence: 99%